2018
DOI: 10.3390/catal8020070
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Synthesis of Nest-Like Microsphere with Exposed (001) Facets and Its Enhanced Photocatalytic Performance by NaOH Alkalization

Abstract: Abstract:In this study, we completed a simple low-temperature synthesis of nest-like titanium oxide (TiO 2 ) microspheres with exposed (001) facets. For the first time, the photocatalytic performance was enhanced by sodium hydroxide (NaOH) alkalization. The characterization of as-synthesized F-TiO 2 and OH-TiO 2 were analyzed by field emission scanning electron microscopy, high-resolution transmission electron microscopy, X-ray diffraction, fourier transform infrared spectroscopic analysis, ultraviolet-vis dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“… 27 The broad emission band centered at 400 nm is ascribed to bound exciton emission due to the trapping of free excitons by titanate groups near defects. 41 Therefore, it can be inferred that Cu 2 O@TiOF 2 /TiO 2 can improve the electron–hole recombination and exhibit high photocatalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“… 27 The broad emission band centered at 400 nm is ascribed to bound exciton emission due to the trapping of free excitons by titanate groups near defects. 41 Therefore, it can be inferred that Cu 2 O@TiOF 2 /TiO 2 can improve the electron–hole recombination and exhibit high photocatalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…2 /TiOF 2 nanohybrids, except OH-S2. It was concluded that TiO 2 /TiOF 2 nanohybrids can adsorb more OH to enhance photocatalytic performance[31][32][33][34][35][36][37].…”
mentioning
confidence: 99%
“…Figure 6 displays the FT-IR spectra of GO, RGO and RGO-P25. The absorption peaks at 3420 cm −1 and 1634 cm −1 , which could be ascribed to the adsorbed water molecules on the particles [36,37].…”
Section: Uv-vis Diffuse Reflection Spectra Analysismentioning
confidence: 97%